ENHANCING THE SANDY SOIL NITROGEN CONTENT OF THE SAMAS COASTAL AREA USING ANAEROBIC DIGESTION SLUDGE DERIVED FROM PALM OIL MILL EFFLUENT - Nina Anggita Wardani; Ahmad Rif'an Khoirul Lisan; Dwi Amalia; Tesa Oktafira Dewanti; Aldy Putra Pratama; Rizki Amanda Putra; Katon Dwi Yudhanto; Hilmaniya Shofia Azzahra (JOURNAL OF TROPICAL SOILS, 2026)
Sandy coastal soils, characterized by poor fertility and low nitrogen (N) content, present significant challenges for sustainable agriculture. This study investigates the potential of anaerobic digestion (AD) sludge derived from palm oil mill effluent (POME) as an organic amendment to enhance soil N in Samas Beach’s degraded sandy soils. Using a completely randomized design (CRD), six digestate application rates (0–800 mL/kg soil) were tested over a 30-day incubation period. Results demonstrated a strong linear dose-response relationship (R² = 0.995), with the highest treatment (A5: 800 mL/kg) increasing soil N by 140% (0.005% to 0.012%) compared to the control. The Kjeldahl method confirmed efficient mineralization of organic N into plant-available NH₄⁺ and NO₃⁻, supported by microbial activity from cow dung inoculum. Tukey’s HSD test revealed all treatments significantly improved N content (p < 0.05), with 400 mL/kg (A4) identified as the optimal rate—balancing efficacy (0.011% N) with economic and environmental practicality. This study highlights POME-derived sludge as a cost-effective, sustainable alternative to synthetic fertilizers for rehabilitating coastal soils, aligning with circular economy principles by valorizing agro-industrial waste.